Hubungan Peran Keluarga Sebagai Pengawas Menelan Obat (Pmo) Dan Persepsi Pasien Dengan Kepatuhan Minum Obat Penderita TBC Di Puskemas Deket Kabupaten Lamongan Tahun 2020 - Arifal Aris Aris; Dian Nurafifah; Novi Sagita (Jurnal Kesehatan, 2021)
ABSTRAK Introduction : Pulmonary tuberculosis (TB) is a chronic disease that is still a global health problem Problem : The purpose of this study was to determine the relationship of the role of the family as the Superintendent of Swallowing Medication (PMO) and the perception of the paisen with adherence to taking medication for TB patients at the Puskesmas Deket Lamongan Design : The design of this study using population correlation analytics is all patients treated at poly tuberculosis as many as 25 patients using the technique of total sampling data collection using a questionnaire. Data analysis uses the Spearman Rank (Rho) test. Analysis : Showed that respondents who have a family role as supervisors of swallowing medicine (PMO) are less with adherence to taking non-compliant medication as many as 20 respondents (80%) and have a role as supervisor of swallowing medicine (PMO) less with adherence to obedient taking medication as much as 1 respondent (40% ). Shows that respondents who have less perception of adherence to taking non-compliant medication as many as 18 respondents (72%) and have less perception of compliance with taking obedient medication as much as 1 respondent (4%). With a value of a = 0.01, the value of p = 0,000 obtained means that there is a relationship between the role of the family as the supervisor of swallowing drugs with adherence to take medication for TB patients at the Puskesmas Deket Lamongan. Value a = 0.05 obtained p value = 0.017 means that there is no relationship between the perception of patients with adherence to taking medication for tuberculosis patients at the Deket Lamongan Health Center. It is expected that people with Tuberculosis (TB) and families with Tuberculosis (TB) can understand the importance of the role of the family in taking medication compliance with Tuberculosis (TB) patients and the importance of positive patient perceptions can affect the success in taking medication compliance. Discussion : To overcome the problem of tuberculosis patients, especially in obedience to talking medication, one of them is the role of the family as the supervisor of swallowing the drug Keywords : PMO, Perception, Compliance